2004
DOI: 10.1165/rcmb.2003-0091oc
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein-D, a Mediator of Innate Lung Immunity, Alters the Products of Nitric Oxide Metabolism

Abstract: Surfactant protein (SP)-D, a 43-kD multifunctional collagen-like lectin, is synthesized and secreted by the airway epithelium. SP-D knockout (SP-D [-/-]) mice exhibit an increase in the number and size of airway macrophages, peribronchiolar inflammation, increases in metalloproteinase activity, and development of emphysema. Nitric oxide (NO) is involved in a variety of signaling processes, and because altered NO metabolism has been observed in inflammation, we hypothesized that alterations in its metabolism wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
56
1
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 39 publications
6
56
1
8
Order By: Relevance
“…However, after the induction of oxidative stress, modification of critical cysteines in Sftpd by reactive species such as nitric oxide leads to a change in its activity to a proinflammatory mediator (15). Findings of persistent localization of macrophages in the lung and increased production of ROS and RNS by these cells in mice lacking native Sftpd are consistent with its anti-inflammatory function (16,17). In previous studies, we demonstrated that inflammatory macrophages and mediators they release play key roles in lung injury and oxidative stress induced by ozone (3,18,19).…”
mentioning
confidence: 82%
“…However, after the induction of oxidative stress, modification of critical cysteines in Sftpd by reactive species such as nitric oxide leads to a change in its activity to a proinflammatory mediator (15). Findings of persistent localization of macrophages in the lung and increased production of ROS and RNS by these cells in mice lacking native Sftpd are consistent with its anti-inflammatory function (16,17). In previous studies, we demonstrated that inflammatory macrophages and mediators they release play key roles in lung injury and oxidative stress induced by ozone (3,18,19).…”
mentioning
confidence: 82%
“…Therefore, even under a mild oxidative stress, one would predict that higher oxide chemistry of NO (i.e., the nitration of tyrosine, lipids, DNA, and the formation of nitrate) would occur. We have shown that even the minor inflammatory lung disease that occurs in surfactant protein D knockout mice results in a major shift from lower to higher oxide chemistry within the tissue and in the lung lining (14).…”
Section: Redox Chemistry Of Nomentioning
confidence: 96%
“…Белок SP-D имеет молекулярную массу 43 кДа, со-стоит из 375 аминокислот, включает 4 домена: NH 2 -хвостовой до-мен, коллагеноподобный домен, домен «шейки» и С-концевой лектиновый домен «головка», распознающий группы COOH-углеводов. SP-D может существовать в форме мономера, триме-ра, додекамера или мультимера [17,20,21]. Процесс олигомери-зации мономеров SP-D в тример вовлекает домены «шейка» и «головка», 4 тримера могут соединяться и формировать додека-мер, додекамеры могут объединяться и формировать мультимер.…”
Section: терапевтический архив 1 2015unclassified
“…Это связывают с тем, что мультимеры и додекамеры SP-D взаимодействуют с ре-цепторами одного типа на поверхности альвеолярных макрофа-гов, тогда как S-нитрозилированные тримеры и мономеры -с рецепторами другого типа. Открытые S-нитрозилированные хво-стовые домены моно-и тримеров SP-D связываются с кальрети-кулином и CD-91 комплексом [17,21], приводя к фосфорилиро-ванию внутриклеточной киназы р38, активации NF-κB и усиле-нию продукции провоспалительных медиаторов и оксида азота. Oксид азота еще больше разрушает мультимеры SP-D, а образую-щиеся моно-и тримеры еще больше усиливают воспалительный ответ и бактерицидную активность макрофагов.…”
Section: терапевтический архив 1 2015unclassified